Descriptive Analysis of Components of Emergency Medicine Residency Program Websites - Pollock, Jordan R. (West J Emerg Med, 2021)
INTRODUCTION: Most emergency medicine (EM) applicants use the internet as a source of information when evaluating residency programs. Previous studies have analyzed the components of residency program websites; however, there is a paucity of information regarding EM program websites. The purpose of our study was to analyze information on EM residency program websites. METHODS: In April–May 2020, we evaluated 249 United States EM residency program websites for presence or absence of 38 items relevant to EM applicants. Descriptive statistics were performed, including means and standard deviations. RESULTS: Of the 249 EM websites evaluated, the websites contained a mean of 20 of 38 items (53%). Only 16 programs (6%) contained at least three-quarters of the items of interest, and no programs contained all 38 items. The general categories with the least amount of items were social media use (9%), research (46%), and lifestyle (49%), compared to the other general categories such as application process (58%), resident information (63%), general program information (67%), and facility information (69%). The items provided by programs most often included program description (98%), blocks and rotations (91%), and faculty listing (88%). The items provided least often included housing/neighborhood information (17%) and social media links (19%). CONCLUSION: Our comprehensive review of EM residency websites in the US revealed the absence of many variables on most programs’ websites. Use of this information to enhance accessibility of desired information stands to benefit both applicants and programs in the increasingly competitive specialty of EM.